Comparison of clinical outcome in acute inferior wall myocardial infarction based on culprit artery: right coronary artery vs left circumflex artery. (26th April 2021) - Altarejos, F; Barea, C; Hernandez-Meneses, BG; Hidalgo-Urbano, R; Almendro-Delia, M; Recio-Mayoral, A; Garcia-Rubira, JC
Abstract: Funding Acknowledgements: Type of funding sources: None. INTRODUCTION: Acute inferior wall myocardial infarction (AIWMI) is related to Right Coronary Artery (RCA) occlusion in about 80% of cases and to Left Circumflex Artery (LCX) in the rest of them, in most series. However it has not been established yet if there is a difference in prognosis depending on culprit artery. PURPOSE: This study compares clinical outcome during hospital stay between RCA-related and LCX-related AIWMI. METHODS: We analysed all patients with AIWMI admitted to the Cardiac Care Unit between August 2011 and February 2019, both ST-elevation (STEMI) and non ST-elevation myocardial infarction, and whose culprit artery was either the RCA or the LCX. Basal characteristics and clinical outcome during hospital stay were compared between RCA and LCX. RESULTS: Among 2252 patients with acute coronary syndrome, 650 were AIWMI. Among them, the culprit artery was the RCA in 461, the LCX in 149, and other or not defined in 30. The mean age was 61.7 ± 11.6 years, 79% of them were male and 21% female. They had a history of current smoking in 50.7%, diabetes mellitus in 24.4%, hypertension in 52.1%, dyslipemia in 44.3% and obesity in 28.7%, without differences between RCA and LCX. RCA patients presented as STEMI in 93.3% vs 87.2% of LCX patients (p = 0.025). Among those presenting as STEMI, 84.4% of RCA and 90.8% of LCX underwent primary coronary intervention. Mean ejection fraction was 50.8% in RCA and 51.2% in LCX. Three-vessel or left main disease was present in 10.2% of RCA and 10.8% of LCX. There was atrioventricular block in 17.8% of RCA and 3.4% of LCX (p < 0.001); atrial fibrillation in 10.2% of RCA and 11.4% of LCX, ventricular fibrillation in 10.4% of RCA and 7.4% of LCX. Median of peak CPK was 1203 in RCA, vs 1785 in LCX (p < 0.001). There was cardiogenic shock (CS) at admission in 5.4% of RCA vs 1.3% of LCX, (p = 0.038) and CS whenever the hospital stay in 8.4% vs 4.0% (p = 0.072). In-hospital mortality was 3.3% in RCA and 3.4% in LCX. Several models of multivariate logistic regression analysis did not find a predictive value of the culprit artery in the development of CS or in-hospital mortality. CONCLUSION: AIWMI related to LCX have greater enzymatic size than those related to RCA. However, RCA infarctions present more often atrioventricular block and cardiogenic shock at admission. Multivariate analysis did not shock significant differences in the development of CS or in-hospital mortality.